Intensity Differences in Playing Online Games Against Child Aggression - ., Yufiarti; ., Qorina; Syukri Sitoru, Ahmad (International Journal of Engineering and Technology, 2018)
This study aims to examine differences in the intensity of playing online games on children's aggressive behavior. The sample consisted of 120 children aged 8 years in Jakarta through survey research. The results of the study concluded that the difference between the intensity of playing online games against children's aggressiveness. The higher the intensity of playing online games will have an impact on the high level of aggressive children, so the role of parents is very necessary.Â Â